TRANSFORMATION OF INDONESIAN LANGUAGE LEARNING WITH ARTIFICIAL INTELLIGENCE APPLICATIONS: THE ERA OF THE INDEPENDENT CURRICULUM FOR LEARNING IN UNIVERSITIES IN INDONESIA - Renika Hasibuan; Ida Bagus Made Wisnu Parta; Husna Imro'athush Sholihah; Antono Damayanto; Farihatun (CV. ADIBA AISHA AMIRA, 2023)
This paper examined the transformation of Indonesian language learning in universities in Indonesia through the integration of artificial intelligence (AI) applications within the context of the Independent Curriculum for Learning. The study investigates the role of AI in enhancing language learning outcomes and the practical implications for educational institutions. Integrating AI applications has brought a paradigm shift in how the Indonesian language is imparted in universities nationwide. As per the research, incorporating AI tools such as chatbots, speech recognition technology, and automated assessment systems has significantly enhanced language learning outcomes, offered students personalized learning experiences, and improved speaking skills. The Independent Curriculum for Learning has empowered students with the flexibility to customize their learning paths and actively participate in the learning process. Furthermore, the evaluation and feedback mechanisms have instilled a culture of continuous improvement and student-centric learning approaches. These insights are precious for educational institutions to effectively integrate AI technologies into their language learning programs, enabling interactive and personalized learning experiences. Further research should explore innovative methods to maximize the benefits of AI in language learning, thereby uplifting educational outcomes to new heights. In conclusion, integrating AI applications in Indonesian language learning has revolutionized traditional teaching methods, promoting interactive and personalized learning experiences. The Independent Curriculum for Learning further supports this transformation, fostering student engagement and empowerment. Future research should explore innovative ways to leverage AI in language learning to enhance educational outcomes.